Respuesta :
Answer:
DF = 57
Step-by-step explanation:
DE + EF = DF
(4x + 10) + (2x - 1) = 9x - 15
Combine like terms on the left side
6x + 9 = 9x - 15
Subtract 6x on both sides
9 = 3x - 15
Add 15 on both sides
24 = 3x
Divide by 3 on both sides
x = 8
DF = 9x - 15 = 9(8) - 15 = 72 - 15 = 57
Checking:
(4(8) + 10) + (2(8) - 1) = 9(8) - 15
(32 + 10) + (16 - 1) = 72 - 15
58 - 1 = 72 - 15
57 = 57
Answer:
DF= DE+EF
9x–15 = (4x+10)+(2x-1)
9x–15 = 6x +9
9x–6x= 9+15
3x = 24
x=24/3
x=8
DF = 9x –15 = 9(8)–15= 72 –15 = 57
So; DF = 57
I hope I helped you^_^